Clinical efficacy and safety of high-dose ambroxol in the form of oromucosal spray in postnasal drip syndrome: results of a multicenter study in Ukraine - Deeva , Yu.V.; co-authors, et al. (Medicni Perspektivi, 2025)
Postnasal drip syndrome (PNDS) is one of the most common clinical conditions in the practice of otolaryngologists and family physicians, characterized by the drainage of mucous or mucopurulent secretions along the posterior wall of the pharynx and accompanied by rhinorrhea, nasal congestion, cough, and a feeling of irritation in the throat. Epidemiological studies show that approximately 20% of the adult population and 15% of children regularly suffer from manifestations of postnasal drip. The pathogenetic mechanisms of the development of PNDS are mucus hypersecretion, impaired rheological properties, dysfunction of mucociliary clearance, and local inflammation. The aim of our study was to clinically evaluate the efficacy and safety of different dosage regimens of the drug "Respx® Spray" (ambroxol) for postnasal drip on the background of common respiratory diseases. A large-scale prospective observational multicenter study was conducted, which included 1867 patients aged 12 to 65 years from 15 regions of Ukraine. The study lasted from September 2023 to March 2024. Patients had various respiratory diseases accompanied by postnasal drip: rhinopharyngitis (47.3%), acute rhinosinusitis (34.0%), vasomotor rhinitis (7.4%), tonsillopharyngitis (4.6%), acute tracheobronchitis (3.8%) and laryngitis/laryngotracheitis (2.9%). The effectiveness of the use was assessed by the dynamics of the intensity of postnasal drip on a 5-point scale at the beginning and on the 5-7th day of treatment. The safety of the drug was monitored by registering and analyzing adverse reactions. The results of the study showed a statistically significant decrease in the intensity of postnasal drip from 4.28±0.03 to 0.91±0.03 points on the 5th day of therapy (p<0.001). The highest efficiency was recorded with the dosage regimens of 4 sprays 4 times a day (decrease to 0.38±0.10 points) and 3 sprays 2 times a day (decrease to 0.60±0.15 points). Subjective assessment of the dynamics of symptoms by patients showed a rapid development of the therapeutic effect – already on the 2nd day of treatment, patients noted a moderate improvement (1.55±1.19 points), and on the 5th day a significant improvement was observed (4.66±0.99 points). The highest subjective improvement rates were recorded in patients with hypertrophic rhinitis (4.56±0.08 points) and tracheitis/acute bronchitis/acute tracheobronchitis (4.52±0.15 points). Overall satisfaction with the treatment was extremely high – 76.4% of patients rated it at 9-10 points on a 10-point scale, another 20.3% – at 7-8 points. Multivariate regression analysis revealed that the effectiveness of the treatment was significantly influenced by factors such as the dosage regimen (p<0.01), the initial intensity of the symptom (p<0.001) and the underlying disease (p<0.05). Non-serious adverse reactions were observed in only 1.2% of patients, which is a fairly low rate and indicates a good safety profile of the drug. The obtained data indicate that ambroxol in the form of a high-dose oromucosal spray is an effective and safe means for alleviating the manifestations of postnasal drip, ensuring high compliance and patient satisfaction. The choice of dosage regimen should be made taking into account the nature of the underlying disease and the initial intensity of postnasal drip syndrome. The safety of the preparation was monitored through registration and analysis of adverse reactions. The results of the study established a statistically significant reduction in the intensity of postnasal dripping from 4.28±0.03 to 0.91±0.03 points on the 5th day of therapy (p<0.001). The highest clinical efficacy was observed with dosing regimens of 4 jets 4 times a day (reduction to 0.38±0.10 points) and 3 jets 2 times a day (reduction to 0.60±0.15 points). Patients' subjective assessment of symptom dynamics indicated a rapid development of therapeutic effect – by the 2nd day of treatment, patients noted moderate improvement (1.55±1.19 points), and by the 5th day, significant improvement in condition was observed (4.66±0.99 points). The highest indicators of subjective improvement were recorded in patients with hypertrophic rhinitis (4.56±0.08 points) and tracheitis/acute bronchitis/acute tracheobronchitis (4.52±0.15 points). Overall treatment satisfaction was exceptionally high – 76.4% of patients rated it at 9-10 points on a 10-point scale, while another 20.3% gave it 7-8 points. Multivariate regression analysis revealed that treatment efficacy was significantly influenced by factors such as dosing regimen (p<0.01), baseline symptom intensity (p<0.001), and underlying disease (p<0.05). The obtained data indicate that ambroxol in the form of oromucosal spray is an effective and safe remedy for the treatment of postnasal syndrome of various etiologies, providing high compliance and patient satisfaction. The selection of dosing regimen should be tailored according to the nature of the underlying disease and the baseline intensity of the postnasal syndrome.